IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) PADA KURIKULUM MERDEKA DI MIN 3 SUKOHARJO - Praptiningsih, Praptiningsih; Udl-Hiyah, Nurul Aulia Lilatul (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The objectives of this research are; 1) to find out how P5 is planned at MIN 3 Sukoharjo; 2) to find out how P5 is implemented at MIN 3 Sukoharjo; 3) to find out the P5 evaluation at MIN 3 Sukoharjo. This research uses a qualitative approach with data collection techniques of observation, documentation, and interviews. The data analysis technique used is the Miles & Huberman model, namely data collection, data reduction, data display, and conclusion drawing/verification. Testing the validity of the data in this research uses a data credibility test with extended observations, increasing persistence and triangulation. The results of this research are that the implementation of P5 at MIN 3 Sukoharjo includes 3 stages, namely; stage 1) Planning, including; designing time allocation, forming an implementation team, determining the topic or theme, determining the model to be used, and designing the P5 module; 2) Implementation, P5 is carried out in all classes from class 1 to class 6 with each class teacher in charge with the stages of project introduction, explanation of objectives, explanation of steps and art performance/work title; 3) evaluation, evaluation is carried out by the teacher in charge of P5 in each class in the form of phase assessment rubrics, daily journals, assessment rubrics, presentations, portfolio assessment rubrics, and final assessment rubrics in formative and summative assessments.